Analysis of wavefront effects for large-aperture tiled-grating compressor. (29th January 2018) - Zhang, S.; Zhang, J. W.; Zhou, Y.; Su, J. Q.; Wang, X.; Deng, B.; Hu, D. X.
Abstract: Monolithic large-aperture diffraction grating tiling is desired to increase the output capability of multi-kilojoule petawatt laser facilities. However, the wavefront errors of input pulse and gratings will degrade the focal spot quality and the compressibility of the output pulse. In this work, the effects of wavefront error of input pulse, deformation and wave aberration of the grating for the large-aperture tiled-grating compressor are investigated theoretically. A series of numerical simulations are presented to discuss the changing trends of focal spot energy caused by wavefront error of input pulse and obtain the error tolerance for specific goals. The influences of coating stress and the wave aberration of holographic exposure gratings on the diffraction wavefront are also discussed. Some advice is proposed for improving the performance of large-aperture tiled-grating. This work paves the way for the design of practical large-aperture tiled-grating compressor for ultrahigh intensity laser facilities in the future.